Evaluation of the colchicine-like activity of Gloriosa superba-extracted fractions for mosquito (Diptera: Culicidae) cytogenetic study - Choochote W. (2014)
Four fractions of Gloriosa superba L., i.e., hexane fraction, dichloromethane fraction 1, dichloromethane fraction 2, and methanol fraction, were investigated for colchicine-like activity using a mosquito cytogenetic assay. The results revealed that the latter three fractions yielded promisingly high colchicine-like activity, whereas the hexane fraction yielded very low activity compared with 1% colchicine in a 0.85% sodium chloride solution. The metaphase rates and average number of metaphase chromosomes per positive brain ganglion (range) of Aedes aegypti L. larvae after incubation with 0.25-2% solutions of dichloromethane fraction 1, dichloromethane fraction 2, 0.5-2% solutions of methanol fraction, and 1% colchicine solution were 90-100% and 7 (2-19) to 22 (7-47); 90-100% and 4 (1-11) to 30 (4-73); 95-100% and 11 (1-28) to 17 (2-62); and 100% and 6 (2-11), respectively. The temperature stability tests of the three promising fractions were performed by heating 0.5% working solution at 121°C for 15 min and preparing 0.5% working solution from stock frozen at -20°C for 10 mo. These fractions also yielded satisfactory outcomes of metaphase rates and an average number of metaphase chromosomes per positive brain ganglia compared with 1% colchicine solution.